Circulatory system learning through student facilitators and explaining in terms of cognitive learning outcomes - Much Fuad Saifuddin; Qistiana Merdikawati; Lenny Yunitasari; Nida Dwi Handayani; Fasaila Nadif Widyati; Afni Nurvita Damayanti Sumarno; Azhar Fauzi; Moch Yusuf Firnandho ZA (STKIP Persada Khatulistiwa Sintang, 2020)
The circulatory system knowledge is essential to be mastered by junior high school students. This study aims to determine the effect of the student facilitator and explaining (SFAE) learning model on the learning outcomes of the circulatory system material in grade VIII students of Muhammadiyah 8 Yogyakarta Middle School. This type of research was quasi-experimental research, with the design used a nonequivalent control group design. The population in this study were all students of class VIII SMP Muhammadiyah 8 Yogyakarta in the academic year 2019/2020. The study sample involved 54 students divided into two classes taken by purposive sampling based on the value of daily tests that had been done previously. The research instrument was a test in the form of pretest and posttest questions. The results obtained were the application of the SFAE learning model in class VIII C of Muhammadiyah 8 Yogyakarta Middle School influencing the learning outcomes of students, as evidenced by the results of the hypothesis test using the Mann Whitney u-test, the significant results obtained 0,000 <0.05. The SFAE learning model influences the cognitive learning outcomes of students on the circulatory system material.Keywords: Learning outcomes, learning activeness, circulatory system, facilitator and explaining learning